Bioactive glass material, oral care composition, toothpaste and preparation method thereof

By using bioactive glass materials with specific crystal structures, the problem of slow dissolution of existing materials is solved, and faster dentin tubular sealing and dentin-sensitive treatment effects are achieved.

CN119874186AActive Publication Date: 2025-04-25ZHAOQING SANJIANG SILICON MATERIALS CO LTD

Patent Information

Application Number
CN202411979987.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing bioactive glass materials are slow to dissolve under the action of water or body fluids, resulting in insufficient response speed in dentin sensitive treatment and inability to effectively seal dentin tubules.

Method used

Bioactive glass materials with specific crystal structures are used. Under the action of water or body fluids, the material can dissolve calcium, phosphorus, silicon and other elements faster, and generate silicon glass networks and hydroxyapatite, thereby reacting with the tooth surface faster and realizing the surface of the dentin.

Benefits of technology

Faster dentin tubular sealing and dentin sensitivity relief or treatment are achieved, improving the therapeutic effect of toothpaste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874186A_ABST
    Figure CN119874186A_ABST
Patent Text Reader

Abstract

The invention relates to a bioactive glass material, an oral care composition, toothpaste and a preparation method thereof. The bioactive glass material belongs to a Na2O-CaO-SiO2-P2O5 system and is prepared from the following components in percentage by weight: 40 to 60 percent of SiO2, 1 to 10 percent of P2O5, 18 to 30 percent of CaO and 10 to 30 percent of Na2O. An X-ray diffraction pattern of the bioactive glass material comprises diffraction peaks with the following 2 theta angle values: 33.6 + / -0.2 degrees and 34.2 + / -0.2 degrees. The bioactive glass material provided by the invention has a special crystal structure, elements such as calcium, phosphorus, silicon and the like can be dissolved out more quickly, a silica glass network and hydroxyapatite are generated, the bioactive glass material can react with the tooth surface more quickly, remineralization of the dentin surface is realized, and the effect of relieving or treating dentin hypersensitivity is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of oral care; more specifically, it relates to a bioactive glass material, an oral care composition, a toothpaste and a preparation method thereof. Background Art

[0002] Dentin is an important component of teeth. Dentin tubules are arranged and distributed in dentin, radiating from the pulp end to the enamel-dentin interface. It is generally believed that when the openings of the dentinal tubules are exposed on the surface of the dentin, when they encounter cold, hot, sour, sweet, mechanical or chemical stimuli, the pulp nerve endings are excited, producing short-term pain, which is the symptom of dentin sensitivity. Studies have shown that compared with individuals with insensitive dentin, individuals with sensitive dentin have more open dentinal tubules and a larger average diameter. Therefore, dentin sensitivity can be alleviated or treated by blocking the dentinal tubules to reduce the permeability of dentin.

[0003] According to the mechanism of action of the plugging, the plugging can be divided into physical plugging and chemical plugging. Among them, the chemical plugging material can bond with the teeth to play a plugging role. The materials currently used for chemical plugging include bioactive glass, fluoride, etc.

[0004] Among bioactive glasses, the most common one is 45S5 bioglass, which is made of Na 2 O, CaO, SiO 2 and P 2 O 5 The formed Na 2 O-CaO-SiO 2 -P 2 O 5 system, by using the common Na 2 O-CaO-SiO 2 Adding P to the glass system 2 O 5 , making the material close to natural human bones in terms of elemental composition. 2 O 5 The addition of increases the biological activity.

[0005] When this bioactive glass is exposed to water or body fluids, the bioactive glass with silica as the main network generator can form a silica gel film during the hydrolysis process. In addition to absorbing calcium and phosphorus ions, the gel film can also resist the dissolution of calcium and phosphorus ions due to its narrow ion channels, thereby accelerating the repair of dentinal tubules. The calcium and phosphorus elements in the bioactive glass will crystallize into mixed hydroxy-carbonate apatite (commonly known as "hydroxyapatite") on the surface of the teeth. Hydroxyapatite is deposited on the surface of the teeth, producing mineralization to block the exposed dentinal tubules.

[0006] It can be seen that silicon, calcium and phosphorus in bioactive glass play an important role in sealing exposed dentinal tubules. The dissolution rate of silicon, calcium and phosphorus in bioactive glass determines whether the bioactive glass can react faster under the action of water or body fluids, seal exposed dentinal tubules faster, and thus relieve or treat dentin sensitivity.

[0007] Due to the influence of various factors such as the molecular arrangement order and molecular forces, the molecular lattice space arrangement of solid substances is different, and the crystal structure formed is called the crystal form. Generally speaking, the crystal form of solid substances has a lower dissolution rate than its amorphous form. The reason is that the dissolution process of solid substances with crystal forms needs to overcome the lattice energy, which limits the solubility and dissolution rate of the substance. The amorphous structure does not need to overcome the lattice energy due to the lack of long-range ordered structure. Therefore, under normal circumstances, amorphous structures have higher apparent solubility and faster dissolution rates. Summary of the invention

[0008] In view of the above existing technical problems, the purpose of the present invention is to provide a bioactive glass material. The bioactive glass material has a special crystal structure, and in a specific application process, compared with the existing amorphous bioactive glass, it can dissolve elements such as calcium, phosphorus, and silicon faster to generate a silicon glass network and hydroxyapatite, and can react with the tooth surface faster to achieve remineralization of the dentin surface, thereby alleviating or treating dentin sensitivity.

[0009] The second object of the present invention is to provide a method for preparing the bioactive glass material.

[0010] The third object of the present invention is to provide a use of a bioactive glass material in blocking dentin tubules or in preparing an oral care composition.

[0011] A fourth object of the present invention is to provide an oral care composition.

[0012] A fifth object of the present invention is to provide a toothpaste.

[0013] The above-mentioned purpose of the present invention is achieved through the following technical solutions.

[0014] The present invention claims a bioactive glass material, the bioactive glass material belongs to Na 2 O-CaO-SiO 2 -P 2 O 5 Systems, in percent by weight, consisting of: SiO 2 40-60%, P 2 O 5 1-10%, CaO 18-30%, Na2 O10-30%; the X-ray diffraction spectrum of the bioactive glass material comprises diffraction peaks with the following 2θ angle values: 33.6±0.2°, 34.2±0.2°.

[0015] In some embodiments, the bioactive glass material has an X-ray diffraction pattern comprising diffraction peaks at the following 2θ angle values: 20.2±0.2°, 23.8±0.2°, 26.5±0.2°, 26.8±0.2°, 33.6±0.2°, 34.2±0.2°, and 48.6±0.2°.

[0016] In some embodiments, the bioactive glass material has an X-ray diffraction pattern comprising diffraction peaks at the following 2θ angle values: 19.1±0.2°, 20.2±0.2°, 20.7±0.2°, 22.0±0.2°, 23.6±0.2°, 23.8±0.2°, 26.5±0.2°, 26.8±0.2°, 26.9±0.2°, 31.9±0.2°, 32.1±0.2°, 33.6±0.2°, 34.2±0.2°, and 48.6±0.2°.

[0017] In some embodiments, the bioactive glass material has Figure 1 , Figure 4 or Figure 5 Consistent X-ray diffraction patterns.

[0018] Furthermore, the present invention claims a method for preparing a bioactive glass material, comprising the following steps:

[0019] (1) adding alkali metal silicate and inorganic acid in a co-dropping process, maintaining the solution pH at 2-6 and the reaction temperature at 40-95° C. during the co-dropping process; or

[0020] Alkali metal silicate and inorganic acid are used to perform acid-base co-dropping in the metal salt base solution, and the solution pH is maintained at 2-6 during the co-dropping process, and the reaction temperature is 40-95°C;

[0021] (2) After the reaction in step (1) is completed, calcium oxide is added and stirred; phosphoric acid is added for reaction and stirred; and then sodium-containing alkali solution is added and stirred to prepare a bioactive glass material.

[0022] Furthermore, the present invention claims another method for preparing a bioactive glass material, comprising the following steps:

[0023] (1) adding alkali metal silicate and phosphoric acid in a co-dropping process, maintaining the solution pH at 3-10 and the reaction temperature at 40-95° C. during the co-dropping process; or

[0024] Alkali metal silicate and phosphoric acid are used in the metal salt base solution for acid-base co-dropping, and the solution pH is maintained at 3-10 during the co-dropping process, and the reaction temperature is 40-95°C;

[0025] (2) After the reaction in step (1) is completed, calcium oxide is added and stirred; then, an alkali solution containing sodium is added and stirred; and a bioactive glass material is prepared.

[0026] Furthermore, the present invention claims another method for preparing a bioactive glass material, comprising the following steps:

[0027] S1. Mixing calcium hydroxide slurry and phosphoric acid at 40-95°C for reaction, maintaining pH at 7-9 during the reaction; performing aging treatment after the reaction to obtain reaction liquid A;

[0028] S2. The silica slurry and calcium oxide are mixed and stirred; then a sodium-containing alkali solution is added and stirred to obtain a reaction solution B;

[0029] S3. Mix the reaction liquid A and the reaction liquid B, and dry them to obtain a bioactive glass material.

[0030] Furthermore, the present invention claims the use of the bioactive glass material in blocking dentinal tubules or in preparing an oral care composition.

[0031] Furthermore, the present invention claims protection for an oral care composition, comprising, by weight percentage, 0.1-20% of the bioactive glass material and an orally acceptable auxiliary material.

[0032] Furthermore, the present invention seeks to protect a toothpaste comprising, by weight: 1-10 parts of the above-mentioned bioactive glass material, 20.5-26.5 parts of a thickener, 45-60 parts of a wetting agent, 11-20 parts of an abrasive, 1-5 parts of a foaming agent, 0-3 parts of a colorant, 0-3 parts of a flavoring agent, 0-0.5 parts of a sweetener, and 0-0.5 parts of an antibacterial agent.

[0033] Furthermore, the present invention seeks to protect a toothpaste comprising, by weight: 1-10 parts of the above-mentioned bioactive glass material, 20.5-26.5 parts of a thickener, 45-60 parts of a wetting agent, 11-20 parts of an abrasive, 1-5 parts of a foaming agent, 0.1-3 parts of a colorant, 0.1-3 parts of a flavoring agent, 0.1-0.5 parts of a sweetener, and 0.1-0.5 parts of an antibacterial agent.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) The present invention provides a bioactive glass material with a specific crystal structure. In a specific application process, it can dissolve elements such as calcium, phosphorus, and silicon more quickly to generate a silicon glass network and hydroxyapatite, which can react with the tooth surface more quickly to achieve remineralization of the dentin surface, thereby alleviating or treating dentin sensitivity.

[0036] (2) The pH of the bioactive glass material provided by the present invention is between 8.0 and 10.0. Compared with bioglass with a pH greater than 10, it has a wider range of applications, is less restricted by toothpaste formulations, and has less irritation to the oral mucosa. The bioactive glass material provided by the present invention has the advantages of good biocompatibility, non-toxicity, and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the X-ray diffraction pattern of the bioactive glass material prepared in Example 1.

[0038] Figure 2 and Figure 3 This is the SEM image of the bioactive glass material prepared in Example 1.

[0039] Figure 4 This is the X-ray diffraction pattern of the bioactive glass material prepared in Example 5.

[0040] Figure 5 This is the X-ray diffraction pattern of the bioactive glass material prepared in Example 6.

[0041] Figure 6 This is the X-ray diffraction pattern of the bioactive glass material of Comparative Example 1.

[0042] Figure 7 This is the X-ray diffraction pattern of the bioactive glass material of Comparative Example 2.

[0043] Figure 8 , Fig. 9 and Fig.10 X-ray diffraction patterns of the products of the bioactive glass materials of Example 1, Comparative Example 1 and Comparative Example 2 after artificial saliva mineralization.

[0044] Fig.11 , Fig.12 and Fig.13 The experimental figures are respectively the experimental figures of conducting mineralization and blocking dentinal tubules experiments using bioglass toothpastes prepared from the bioactive glass materials of Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0045] In the following description, certain specific details are set forth to provide a thorough understanding of various embodiments of the present invention. However, those skilled in the art will appreciate that the present invention can be implemented without using these details. The description of multiple embodiments hereinafter is made with the understanding that the present disclosure is to be regarded as an example of the subject matter claimed for protection, rather than being intended to limit the appended claims to the specific embodiments described. The titles used throughout the full text of the present disclosure are merely for convenience and are not to be interpreted as limiting the claims in any way. The embodiments described under any title may be combined with the embodiments described under any other title.

[0046] [Composition and crystal form]

[0047] Due to the influence of various factors such as molecular arrangement order, molecular structure configuration, conformation, molecular forces, eutectic substances, etc., solid substances have different molecular lattice spatial arrangements, forming two or more different crystal structures. This phenomenon is called "polymorphism" or "isomorphism". "Polymorphism" is widely present in solids. Different crystal forms of the same substance may have different physical and chemical properties, such as reaction speed, stability, solubility, dissolution rate, bioavailability, etc. There may be significant differences.

[0048] The crystal form can be determined by a variety of technical means, such as X-ray diffraction (XRD), X-ray powder diffraction (XRPD), infrared absorption spectroscopy (IR), melting point method, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), nuclear magnetic resonance, Raman spectroscopy, solution calorimetry, scanning electron microscopy (SEM), quantitative analysis, solubility and dissolution rate, etc.

[0049] X-ray diffraction (XRD) can detect information such as changes in crystal form, crystallinity, and crystal structure state, and is a common means of identifying crystal forms. Crystalline substances and amorphous substances (amorphous) can be distinguished. The XRD patterns of different crystal forms show differences in the number of diffraction peaks, the position of the diffraction peaks, the intensity of the diffraction peaks, and the shape of the diffraction peaks, so they can be used as fingerprints of crystals for identifying and distinguishing different crystal forms. More specifically, the difference in the crystal structure is mainly determined by the position of the diffraction peaks in the XRD pattern. Therefore, in some embodiments, the bioactive glass provided by the present invention is distinguished from the existing bioactive glass by having certain characteristic peak positions characterized by 2θ angle values ​​and their XRD patterns, which are substantially as shown in the XRD patterns provided in the accompanying drawings of the present invention. Based on the conventional understanding of ordinary technicians in the field, the 2θ angle value of the XRD pattern may have experimental errors, and the 2θ angle value of the XRD pattern may be slightly different between different instruments and different samples. Therefore, the 2θ angle value provided by the present invention cannot be regarded as absolute. According to the instrument conditions used in the test of the present invention, the characteristic diffraction peak characterized by the 2θ angle value has an error tolerance of ±0.2°.

[0050] In addition, when referring to, for example, an XRD pattern or an XRPD pattern, "consistent with a pattern..." does not mean that it is completely consistent with the pattern provided or described herein. When considered by a person of ordinary skill in the art, the pattern that falls within the experimental error or the error tolerance described above should also be taken into account.

[0051] The bioactive glass material provided by the present invention has a specific crystal form. The inventors surprisingly found through research that, compared with the existing amorphous bioactive glass, the bioactive glass material with a specific crystal form provided by the present invention can dissolve calcium, phosphorus, silicon and other elements in the bioactive glass material more quickly when mineralizing and blocking dentinal tubules under the action of water or body fluids, generating a silicon glass network and hydroxyapatite, and then being able to react with the tooth surface more quickly to achieve remineralization of the dentin surface, thereby playing a role in alleviating or treating dentin sensitivity.

[0052] A person skilled in the art can distinguish the bioactive glass material provided by the present invention by the diffraction peaks containing the following 2θ angle values: 33.6±0.2°, 34.2±0.2°. More specifically, in some more detailed X-ray diffraction pattern data, the X-ray diffraction pattern of the bioactive glass material provided by the present invention contains the following diffraction peaks of 2θ angle values: 20.2±0.2°, 23.8±0.2°, 26.5±0.2°, 26.8±0.2°, 33.6±0.2°, 34.2±0.2° and 48.6±0.2°. More specifically, the diffraction peaks comprising the following 2θ angle values: 19.1±0.2°, 20.2±0.2°, 20.7±0.2°, 22.0±0.2°, 23.6±0.2°, 23.8±0.2°, 26.5±0.2°, 26.8±0.2°, 26.9±0.2°, 31.9±0.2°, 32.1±0.2°, 33.6±0.2°, 34.2±0.2° and 48.6±0.2°. More specifically, the bioactive glass material provided by the present invention has substantially the same Figure 1 , Figure 4 or Figure 5 Consistent X-ray diffraction patterns.

[0053] Further, in some embodiments, the bioactive glass material provided by the present invention comprises, by weight percentage: SiO 2 40-60%, P 2 O 5 1-10%, CaO 18-30%, Na 2 O 10-30%.

[0054] SiO as bioactive glass material 2 Non-limiting example of content, SiO 2 The weight percentage can be 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, etc., or an interval range formed by any of the above values, such as 42-50%, 52-58%, etc., but the present invention is not limited thereto.

[0055] As a bioactive glass material 2 O 5 Non-limiting example of content, P 2 O 5 The weight percentage can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, etc., or an interval range formed by any of the above values, such as 1-4%, 3-10%, etc., but the present invention is not limited thereto.

[0056] As a non-limiting example of the CaO content in the bioactive glass material, the weight percentage of CaO can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, etc., or an interval range formed by any of the above values, such as 20-25%, 23-29%, etc., but the present invention is not limited thereto.

[0057] As a bioactive glass material 2 Non-limiting examples of O content, Na 2 The weight percentage of O can be 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, etc., or an interval range formed by any of the above values, such as 12-20%, 16-28%, etc., but the present invention is not limited thereto.

[0058] Illustrative, non-limiting examples of bioactive glass materials consistent with the present invention may have the following features: In one or more embodiments, the bioactive glass material may have an apparent density of 0.5-1.2 g / mL; more specifically, the apparent density may be 0.5-0.7 g / mL. In one or more embodiments, the bioactive glass material may contain 0.3-2.0% moisture; more specifically, 0.3-1.0% moisture. In one or more embodiments, the D50 particle size of the bioactive glass material may be 3.5-4.0 μm; more specifically, the D50 particle size may be 3.5-3.9 μm. In one or more embodiments, the BET specific surface area of ​​the bioactive glass material may be 10-20 m 2 In one or more embodiments, the pore volume of the bioactive glass material may be 0.01-0.2 cm 3 / g; more specifically, the pore volume can be 0.1-0.2cm 3 / g. In one or more embodiments, the pore size of the bioactive glass material may be 10-40nm; more specifically, the pore size may be 35-40nm. In one or more embodiments, the oil absorption value of the bioactive glass material may be 20-100g / 100g; more specifically, the oil absorption value may be 70-85g / 100g. In one or more embodiments, the copper consumption value of the bioactive glass material is 2-4mg. In one or more embodiments, the Ganz whiteness of the bioactive glass material is >98; more specifically, the Ganz whiteness may be 98.5-99.9.

[0059] In one or more embodiments, the pH of the bioactive glass material may be 8.5-10. Compared with existing bioactive glass materials whose pH generally exceeds 10, the pH of the bioactive glass material controlled at 8.5-10 has the advantage of a wider range of applications and less formulation restrictions when prepared into an oral composition; in addition, the pH controlled at 8.5-10 also has the advantage of less irritation to the oral mucosa.

[0060] [Preparation method]

[0061] The bioactive glass material with a specific crystal structure provided by the present invention can be prepared by a variety of methods.

[0062] A non-limiting example of the preparation method according to the present invention can be obtained by the following first preparation method:

[0063] (1) adding alkali metal silicate and inorganic acid in a co-dropping process, maintaining the solution pH at 2-6 and the reaction temperature at 40-95° C. during the co-dropping process; or

[0064] Alkali metal silicate and inorganic acid are used to perform acid-base co-dropping in the metal salt base solution, and the solution pH is maintained at 2-6 during the co-dropping process, and the reaction temperature is 40-95°C;

[0065] (2) After the reaction in step (1) is completed, calcium oxide is added and stirred; phosphoric acid is added for reaction and stirred; and then sodium-containing alkali solution is added and stirred to prepare a bioactive glass material.

[0066] In the above method, as a non-limiting example of calcium oxide, conventional commercially available calcium oxide in the art can be used as a substitute. More specifically, sintered calcium oxide can also be obtained by sintering calcium salts (such as calcium carbonate, etc.). More specifically, in some embodiments, the calcium salt can be continuously roasted using a heat source (such as a muffle furnace, etc.) of not less than 800°C, not less than 850°C, not less than 900°C, not less than 950°C, not less than 1000°C, not less than 1100°C, not less than 1200°C. More specifically, the sintering temperature is 900-1200°C. More specifically, the sintering temperature is 1000-1100°C. The conversion rate of calcium oxide sintered by the above method can be ≥96%, more preferably, the conversion rate is ≥97%, more preferably, the conversion rate is ≥98%, and most preferably, the conversion rate is 100%. At this conversion rate, sintered calcium oxide has higher activity. The conversion rate is calculated as conversion rate Y=△m / 44%m, wherein △m is the mass difference between calcium carbonate before and after burning; m is the mass of calcium carbonate. More specifically, the calcium salt can be calcium carbonate, calcium chloride, calcium bicarbonate or a mixture thereof.

[0067] As a non-limiting example of an alkali metal silicate, the alkali metal silicate may be selected from sodium silicate, potassium silicate or a mixture thereof. In some non-limiting examples, the modulus of the alkali metal silicate may be 1-3.8, and the concentration may be 1-2.9N. More specifically, the modulus of the alkali metal silicate may be 3-3.6, and the concentration may be 1.2-2.6N. More specifically, the modulus of the alkali metal silicate may be 3.1-3.5, and the concentration may be 1.2-2.2N. As a non-limiting example of an inorganic acid, the inorganic acid may be sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid or a mixture thereof. In some non-limiting examples, the concentration of the inorganic acid may be 2-12N. More specifically, the concentration of the inorganic acid may be 4-10N. As a non-limiting example of a metal salt base liquid, it may be a metal salt base liquid formed by combining the anions of the above-mentioned inorganic acid and the alkali metal of the alkali metal silicate, including but not limited to sodium sulfate and the like. In some non-limiting examples, the sodium-containing alkali solution is mainly used to provide the sodium element in the bioactive glass, and can be sodium hydroxide or the like.

[0068] In step (1) of the above method, as a non-limiting example of reaction time, the reaction time of acid-base co-dropping is not less than 0.5h, not less than 1.0h, not less than 1.5h. In some embodiments, the reaction time of acid-base co-dropping is 0.5-1.5h.

[0069] In step (1) of the above method, as a non-limiting example of the reaction temperature, the reaction temperature can be 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc. More specifically, the reaction temperature can be 45-90°C. More specifically, the reaction temperature can be 60-90°C.

[0070] In step (2) of the above method, after adding calcium oxide, the stirring time is not less than 10 minutes, not less than 15 minutes, not less than 20 minutes, not less than 30 minutes, etc. More specifically, the stirring time is 10-30 minutes. The stirring speed can be 100 rpm, 300 rpm, 500 rpm, 700 rpm, 900 rpm, 1000 rpm, etc. More specifically, the stirring speed is 100-1000 rpm. More specifically, the stirring speed is 400-800 rpm.

[0071] In step (2) of the above method, the concentration of phosphoric acid added can be 30-40%, and the reaction time is not less than 0.5h, not less than 1.0h, not less than 1.5h. More specifically, the reaction time is 0.5-1.5h. More specifically, the reaction time is 0.5-1h. After the phosphoric acid reaction is completed, continue stirring, and the stirring time is not less than 10min, not less than 15min, not less than 20min, not less than 30min, etc., more specifically, the stirring time is 10-40min. More specifically, the stirring time is 20-40min. The stirring speed can be 100rpm, 300rpm, 500rpm, 700rpm, 900rpm, 1000rpm, etc. More specifically, the stirring speed is 100-1000rpm. More specifically, the stirring speed is 400-800rpm.

[0072] In step (2) of the above method, sodium-containing alkali solution is added, and the stirring time is not less than 10 minutes, not less than 15 minutes, not less than 20 minutes, not less than 30 minutes, etc. More specifically, the stirring time is 10-40 minutes. More specifically, the stirring time is 20-40 minutes. The stirring speed can be 100 rpm, 300 rpm, 500 rpm, 700 rpm, 900 rpm, 1000 rpm, etc. More specifically, the stirring speed is 100-1000 rpm. More specifically, the stirring speed is 400-800 rpm.

[0073] Furthermore, the present invention provides a second method for preparing a bioactive glass material, which comprises the following steps:

[0074] (1) adding alkali metal silicate and phosphoric acid in a co-dropping process, maintaining the solution pH at 3-10 and the reaction temperature at 40-95° C. during the co-dropping process; or

[0075] Alkali metal silicate and phosphoric acid are used in the metal salt base solution for acid-base co-dropping, and the solution pH is maintained at 3-10 during the co-dropping process, and the reaction temperature is 40-95°C;

[0076] (2) After the reaction in step (1) is completed, calcium oxide is added and stirred; then, an alkali solution containing sodium is added and stirred; and a bioactive glass material is prepared.

[0077] In step (1) of the above method, as a non-limiting example of pH, the pH can be 4, 5, 6, 7, 8, 9, etc., or an interval range formed by any of the above values, such as 4-7, 8-10, etc., but the present invention is not limited thereto.

[0078] In step (1) of the above method, as a non-limiting example of the reaction temperature, the reaction temperature can be 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc. More specifically, the reaction temperature can be 45-90°C. More specifically, the reaction temperature can be 60-90°C.

[0079] In step (1) of the above method, as a non-limiting example of an alkali metal silicate, the modulus of the alkali metal silicate may be 1-3.8, and the concentration may be 1-2.9N. More specifically, the modulus of the alkali metal silicate may be 2-3.6, and the concentration may be 2-2.6N. More specifically, the modulus of the alkali metal silicate may be 3-3.5, and the concentration may be 2.1-2.4N. As a non-limiting example of an inorganic acid, the concentration of the inorganic acid may be 2-12N. More specifically, the concentration of the inorganic acid may be 4-8N. More specifically, the concentration of the inorganic acid may be 5-7N.

[0080] Other specific process parameters of the second bioactive glass material provided by the present invention can refer to the preparation method of the first bioactive glass material mentioned above.

[0081] Furthermore, the present invention provides a third method for preparing a bioactive glass material, which comprises the following steps:

[0082] S1. Mixing calcium hydroxide slurry and phosphoric acid at 40-95°C for reaction, maintaining pH at 7-9 during the reaction; performing aging treatment after the reaction to obtain reaction liquid A;

[0083] S2. The silica slurry and calcium oxide are mixed and stirred; then a sodium-containing alkali solution is added and stirred to obtain a reaction solution B;

[0084] S3. Mix the reaction liquid A and the reaction liquid B, dry them, and crush them to obtain a bioactive glass material.

[0085] As a non-limiting example of the reaction temperature of step S1, the reaction temperature may be 60-90°C; more specifically, 80-90°C. As a non-limiting example of calcium hydroxide slurry, the concentration of calcium hydroxide slurry may be 0.5-1 mol / L; more specifically, 0.6-0.8 mol / L. As a non-limiting example of phosphoric acid, the concentration of phosphoric acid may be 30-40%; more specifically, the concentration of phosphoric acid may be 35-40%.

[0086] In step S2, the sodium-containing alkali solution is mainly used to provide the sodium element in the bioactive glass, and it can be used, for example, sodium hydroxide. In step S2, the stirring time is not less than 10min, not less than 15min, not less than 20min, not less than 30min, etc., and more specifically, the stirring time is 10-40min. More specifically, the stirring time is 20-40min. The stirring speed can be 100rpm, 300rpm, 500rpm, 700rpm, 900rpm, 1000rpm, etc. More specifically, the stirring speed is 100-1000rpm. More specifically, the stirring speed is 400-800rpm. In step S2, the stirring time after adding the sodium-containing alkali solution is not less than 1h, not less than 2h, not less than 3h, not less than 4h, etc., and more specifically, the stirring time is 1-4h.

[0087] [Oral care composition]

[0088] The bioactive glass material provided by the present invention can be used in preparing an oral care composition for blocking dentinal tubules.

[0089] The oral care composition of the present invention can be in any form known in the art suitable for oral care. As non-limiting examples of oral care compositions, the oral care composition can be toothpaste, gel, mouthwash, dental floss, paste, powder, tablet, or liquid preparation used to clean the oral surface, such as dentifrice, tooth gel, tooth paste, oral spray, tooth powder, foam, chewing gum, lipstick, sponge, mouthwash, chewing gum, or denture products, etc.

[0090] An orally acceptable excipient refers to an ingredient in an oral care composition that is suitable for the physiological environment of the oral cavity and does not cause excessive side effects to the oral cavity.

[0091] The present invention provides an oral care composition, comprising, by weight percentage, 0.1-20% of the above-mentioned bioactive glass material and an orally acceptable auxiliary material. The weight percentage of the bioactive glass material in the oral care composition can be 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 15%, 18%, etc., or an interval range formed by any of the above values, such as 1.5-3%, 2-5%, etc., and the present invention is not limited thereto.

[0092] As non-limiting examples of auxiliary materials, they can adopt ingredients conventionally used for oral combination in the art, including but not limited to one or more of thickeners, sweeteners, antibacterial agents, abrasives, wetting agents, pigments or colorants, flavoring agents, and foaming agents.

[0093] Exemplary thickeners include, but are not limited to, carbomer (such as carbomer 940), polyethylene glycol (such as PEG-400), hydroxyethyl cellulose, carboxymethyl cellulose and its salts (e.g., sodium carboxymethyl cellulose), carrageenan, carboxyvinyl polymers, xanthan gum, carrageenan, gelatin, pullulan, sodium alginate, etc. In certain embodiments, the thickener includes one or more of xanthan gum, carrageenan, or sodium carboxymethyl cellulose. Preferably, the thickener is selected from carbomer and / or polyethylene glycol.

[0094] Exemplary sweeteners include, but are not limited to, sodium saccharin, flavoring oils such as spearmint oil, peppermint oil, wintergreen oil, sassafras oil, clove oil, sage oil, eucalyptus oil, cinnamon oil, lemon oil, and orange peel oil, methyl salicylate, and eugenol. Preferably, the sweetener is selected from sodium saccharin.

[0095] Exemplary antimicrobial agents include, but are not limited to, methylparaben, zinc oxide, stannous chloride, tetrahydrocurcumin, cetylpyridinium chloride, triclosan, etc. Preferably, the antimicrobial agent is selected from methylparaben.

[0096] Exemplary humectants include, but are not limited to, glycerol, sorbitol, xylitol, propylene glycol, etc. Preferably, the humectant is selected from glycerol.

[0097] Various other optional ingredients well known in the art may be added to the toothpaste compositions of the present invention to improve the general aesthetic appearance. These ingredients include pigments, dyes, agents for forming stains, and the like.

[0098] Exemplary flavoring agents may be those commonly used in the art, including but not limited to wintergreen essence, mint essence, spearmint essence, sassafras essence, clove essence, and the like.

[0099] Exemplary foaming agents include, but are not limited to, sodium lauryl sulfate, cocamidopropyl betaine, alkyl glucosides, alkyl sulfonates, alkyl benzene sulfonates, and the like.

[0100] Exemplary abrasives include, but are not limited to, silicon dioxide, calcium carbonate, calcium bicarbonate, calcium pyrophosphate, and the like.

[0101] Further, in some embodiments, the present invention provides a toothpaste, comprising, by weight: 1-10 parts of bioactive glass material, 20.5-26.5 parts of thickener, 45-60 parts of wetting agent, 11-20 parts of abrasive, 1-5 parts of foaming agent, 0-3 parts of colorant, 0-3 parts of flavoring agent, 0-0.5 parts of sweetener, and 0-0.5 parts of antibacterial agent. Further, by weight, the toothpaste comprises: 1-10 parts of bioactive glass material, 20.5-26.5 parts of thickener, 45-60 parts of wetting agent, 11-20 parts of abrasive, 1-5 parts of foaming agent, 0.1-3 parts of colorant, 0.1-3 parts of flavoring agent, 0.1-0.5 parts of sweetener, and 0.1-0.5 parts of antibacterial agent.

[0102] Raw material information and test methods

[0103] Test method for apparent density: QB / T2346-2015.

[0104] Copper loss test method: JSJ-C-ZG-36: (1) Take 2 copper sheets, clean them with distilled water, blow dry them with a hair dryer, and place them in a dryer. After 15 minutes, take out the copper sheets with tweezers and weigh the weight W1 (in mg) of the two copper sheets before wear. After weighing, place the copper sheets in the material trough of the hard particle measuring instrument.

[0105] (2) Accurately weigh 20g of bioactive glass material sample and evenly disperse it in 120g of sorbitol solution. Transfer the obtained friction particle slurry to the material tank of the superhard particle measuring instrument, turn on the superhard particle measuring instrument, and make the friction head rub the copper sheet 10,000 times in the test slurry. After the friction is completed, take out the copper sheet with tweezers, rinse it with distilled water, blow it dry with a hair dryer, and place it in a dryer. After 15 minutes, take out the copper sheet with tweezers and weigh its weight after wear W2 (in mg); (3) The copper wear value W = W1-W2 (in mg). The deviation of the parallel experimental results cannot exceed 20%, and the average value is taken as the final result.

[0106] Ganz whiteness test method: QB / T2346-2015.

[0107] Moisture testing method: QB / T2346-2015.

[0108] Particle size test method: GBT19087-2016.

[0109] BET specific surface area, pore volume and pore size test method: The specific surface area, pore volume and pore size of amorphous silica particles were tested using a JW-BK112 static nitrogen adsorption instrument.

[0110] Test method for oil absorption value: ASTM D281.

[0111] pH test method: QB / T2346-2015.

[0112] Bioactive glass 4516, Novamin 4516, 3M.

[0113] ZI-165: Silica, Jinsanjiang.

[0114] Core-shell type: core-shell silica, Jinsanjiang.

[0115] K12: Sodium dodecyl sulfate, Jiangsu Youyang Pharmaceutical Co., Ltd.

[0116] Example 1

[0117] (1) Sintering of calcium carbonate: Take some analytically pure calcium carbonate; put it into a muffle furnace for calcination at 1000°C; after cooling to room temperature, make the conversion rate 100% to obtain sintered calcium oxide. The conversion rate is calculated as follows: Y = △m / 44%m, where △m is the mass difference between calcium carbonate before and after calcination; m is the mass of calcium carbonate.

[0118] (2) Acid-base co-dropping was performed at a reaction temperature of 90°C, the pH value of the acid-base co-dropping process was maintained at 2.5, and the reaction time was 1 hour. The base used was sodium silicate, with a modulus of 3.5 and a concentration of 1.2N. Based on the silicon dioxide generated by the alkali metal silicate accounting for 50% of the total mass of the bioactive glass material, a corresponding mass of alkali metal silicate was added; the acid used was sulfuric acid, with a concentration of 8N.

[0119] (3) After the reaction is completed, add the sintered calcium oxide from step (1), the amount of sintered calcium oxide added is 22% of the total mass of the bioactive glass material, stir at a speed of 600 rpm for 10 minutes, and stir evenly; then add dilute phosphoric acid, the reaction time is 0.6h, the concentration of dilute phosphoric acid is 30%, and the corresponding mass of dilute phosphoric acid is added based on the generated phosphorus pentoxide accounting for 5% of the total mass of the bioactive glass material; after the reaction is completed, continue to stir at 600 rpm for 30 minutes, then add sodium hydroxide, the sodium introduced by sodium hydroxide is calculated as sodium oxide generated, and sodium oxide accounts for 8.2% of the total mass of the bioactive glass material, continue to stir at a speed of 600 rpm for 30 minutes, and discharge.

[0120] (4) spray drying the liquid material discharged from step (3) at an inlet air temperature of 300° C. and an outlet air temperature of 120° C.; crushing the liquid material to a desired particle size to obtain a bioactive glass material.

[0121] The bioactive glass material prepared in this embodiment was analyzed and identified by X-ray diffraction (XRD) analysis using a Bruker D8A A25 X-ray diffractometer, using Cu-Kα radiation, and had the following characteristic peaks represented by angle 2θ: 2θ=19.1±0.2°, 2θ=20.2±0.2°, 2θ=23.8±0.2°, 2θ=26.5±0.2°, 2θ=26.9±0.2°, 2θ=31.9±0.2°, 2θ=32.1±0.2°, 2θ=33.6±0.2°, 2θ=34.2±0.2°, 2θ=48.6±0.2°. The X-ray diffraction pattern of the bioactive glass material prepared in this embodiment is as follows: Figure 1 As shown. The bioactive glass material prepared in Example 1 belongs to Na 2 O-CaO-SiO 2 -P 2 O 5 Systems, by weight percentage, consisting of: SiO 2 50%, P 2 O 5 5%, CaO 22%, Na 2 O 23%.

[0122] The SEM image of the bioactive glass material prepared in Example 1 is as follows: Figure 2 and Figure 3 shown.

[0123] Example 2

[0124] (1) Sintering of calcium carbonate: Take some analytically pure calcium carbonate; put it into a muffle furnace for calcination at 1000°C; after cooling to room temperature, make the conversion rate 100% to obtain sintered calcium oxide. The conversion rate is calculated as follows: Y = △m / 44%m, where △m is the mass difference between calcium carbonate before and after calcination; m is the mass of calcium carbonate.

[0125] (2) Add a metal salt base liquid with a volume ratio of 20% (based on the volume of the reactor (5L)) to the reaction tank. The metal salt base liquid is sodium sulfate. The sodium introduced by sodium sulfate is calculated based on the generated sodium oxide. The sodium oxide accounts for 3% of the total mass of the bioactive glass material. The reaction temperature is 80°C. The acid and base are dripped together. The pH of the acid and base dripping process is maintained at 3.5. The reaction time is 1 hour. The base used is sodium silicate with a modulus of 3.3 and a concentration of 1.5N. The corresponding mass of alkali metal silicate is added based on the silicon dioxide generated by the alkali metal silicate accounting for 40% of the total mass of the bioactive glass material; the acid used is sulfuric acid with a concentration of 4N.

[0126] (3) After the reaction is completed, add the sintered calcium oxide from step (1); the amount of sintered calcium oxide added is 27% of the total mass of the bioactive glass material, stir at a speed of 600 rpm for 15 minutes, and stir evenly; then add dilute phosphoric acid, the reaction time is 0.5 h, the concentration of dilute phosphoric acid is 33%, and the corresponding mass of dilute phosphoric acid is added so that the generated phosphorus pentoxide accounts for 5% of the total mass of the bioactive glass material; after the reaction is completed, continue to stir at 600 rpm for 30 minutes, then add sodium hydroxide, the sodium introduced by sodium hydroxide is calculated as sodium oxide, and the sodium oxide accounts for 12.5% ​​of the total mass of the bioactive glass material, continue to stir at a speed of 600 rpm for 30 minutes, and discharge.

[0127] (4) spray drying the liquid material discharged from step (3) at an inlet air temperature of 300° C. and an outlet air temperature of 120° C.; crushing the liquid material to a desired particle size to obtain a bioactive glass material.

[0128] The bioactive glass material prepared in this example was analyzed and identified by X-ray diffraction (XRD) using a Bruker D8A A25 X-ray diffractometer, using Cu-Kα radiation, and had characteristic peaks expressed by angles 2θ consistent with those in Example 1. The X-ray diffraction pattern was basically as follows: Figure 1 shown.

[0129] Bioactive glass materials belong to Na 2 O-CaO-SiO 2 -P 2 O 5 System, by weight percentage, bioactive glass materials include: SiO 2 40%, P 2 O 5 5%, CaO 27%, Na 2 O 28%.

[0130] Example 3

[0131] (1) Sintering of calcium carbonate: Take some analytically pure calcium carbonate; put it into a muffle furnace for calcination at 1000°C; after cooling to room temperature, make the conversion rate 100% to obtain sintered calcium oxide. The conversion rate is calculated as follows: Y = △m / 44%m, where △m is the mass difference between calcium carbonate before and after calcination; m is the mass of calcium carbonate.

[0132] (2) Add 25% by volume (based on the volume of the reactor (5L)) of a metal salt base liquid to the reaction tank. The metal salt base liquid is sodium sulfate. The amount of sodium introduced is calculated based on the amount of sodium oxide generated. The sodium oxide accounts for 1.3% of the total mass of the bioactive glass material. The reaction temperature is 70°C. The acid and base are added simultaneously. The pH of the acid and base addition process is maintained at 4.5. The reaction time is 1 hour. The base used is sodium silicate with a modulus of 3.2 and a concentration of 1.8N. The corresponding mass of alkali metal silicate is added based on the amount of silicon dioxide generated by the alkali metal silicate accounting for 55% of the total mass of the bioactive glass material. The acid used is sulfuric acid with a concentration of 6N.

[0133] (3) After the reaction is completed, add the sintered calcium oxide from step (1); the amount of sintered calcium oxide added is 22% of the total mass of the bioactive glass material, stir at a speed of 600 rpm for 20 minutes, and stir evenly; then add dilute phosphoric acid, the reaction time is 0.4h, the concentration of dilute phosphoric acid is 35%, and the corresponding mass of dilute phosphoric acid is added so that the generated phosphorus pentoxide accounts for 3% of the total mass of the bioactive glass material; after the reaction is completed, continue to stir at a speed of 600 rpm for 30 minutes, then add sodium hydroxide, the sodium introduced by sodium hydroxide is calculated as sodium oxide generated, and sodium oxide accounts for 1% of the total mass of the bioactive glass material, continue to stir at a speed of 600 rpm for 30 minutes, and discharge.

[0134] (4) spray drying the liquid material discharged from step (3) at an inlet air temperature of 300° C. and an outlet air temperature of 120° C.; crushing the liquid material to a desired particle size to obtain a bioactive glass material.

[0135] The bioactive glass material prepared in this example was analyzed and identified by X-ray diffraction (XRD) using a Bruker D8A A25 X-ray diffractometer, using Cu-Kα radiation, and had characteristic peaks expressed by angles 2θ consistent with those in Example 1. The X-ray diffraction pattern was basically as follows: Figure 1 shown.

[0136] Bioactive glass materials belong to Na 2 O-CaO-SiO 2 -P 2 O 5 System, by weight percentage, bioactive glass materials include: SiO 2 55%, P 2 O 5 3%, CaO 22%, Na 2 O 20%.

[0137] Example 4

[0138] (1) Sintering of calcium carbonate: Take some analytically pure calcium carbonate; put it into a muffle furnace for calcination at 1000°C; after cooling to room temperature, make the conversion rate 100% to obtain sintered calcium oxide. The conversion rate is calculated as follows: Y = △m / 44%m, where △m is the mass difference between calcium carbonate before and after calcination; m is the mass of calcium carbonate.

[0139] (2) Add 30% by volume (based on the volume of the reactor (5L)) of a metal salt base liquid to the reaction tank. The metal salt base liquid is sodium sulfate. The amount of sodium introduced is calculated based on the generated sodium oxide. The sodium oxide accounts for 4% of the total mass of the bioactive glass material. The reaction temperature is 60°C. The acid and base are added simultaneously. The pH of the acid and base addition process is maintained at 5.5. The reaction time is 1 hour. The base used is sodium silicate with a modulus of 3.1 and a concentration of 2.2N. The corresponding mass of alkali metal silicate is added based on the silicon dioxide generated by the alkali metal silicate accounting for 48% of the total mass of the bioactive glass material. The acid used is sulfuric acid with a concentration of 10N.

[0140] (3) After the reaction is completed, add the sintered calcium oxide from step (1); the amount of sintered calcium oxide added is 23% of the total mass of the bioactive glass material, and stir at a speed of 600 rpm for 30 minutes to stir evenly; then add dilute phosphoric acid, the reaction time is 0.3 h, the concentration of dilute phosphoric acid is 40%, and the corresponding mass of dilute phosphoric acid is added so that the generated phosphorus pentoxide accounts for 6% of the total mass of the bioactive glass material; after the reaction is completed, continue to stir at a speed of 600 rpm for 30 minutes, then add sodium hydroxide, the sodium introduced by the sodium hydroxide is calculated as the generated sodium oxide, and the sodium oxide accounts for 3% of the total mass of the bioactive glass material, continue to stir at a speed of 600 rpm for 30 minutes, and discharge.

[0141] (4) spray drying the liquid material discharged from step (3) at an inlet air temperature of 300° C. and an outlet air temperature of 120° C.; crushing the liquid material to a desired particle size to obtain a bioactive glass material.

[0142] The bioactive glass material prepared in this example was analyzed and identified by X-ray diffraction (XRD) using a Bruker D8A A25 X-ray diffractometer, using Cu-Kα radiation, and had characteristic peaks expressed by angles 2θ consistent with those in Example 1. The X-ray diffraction pattern was basically as follows: Figure 1 shown.

[0143] Bioactive glass materials belong to Na 2 O-CaO-SiO 2 -P 2 O 5 System, by weight percentage, bioactive glass materials include: SiO 2 48%, P 2 O 56%, CaO 23%, Na 2 O 23%. The physical and chemical indexes of the bioactive glass materials prepared in Examples 1 to 4 are shown in Table 1 below.

[0144] Table 1

[0145]

[0146] Example 5

[0147] (1) Sintering of calcium carbonate: Take some analytically pure calcium carbonate; put it into a muffle furnace for calcination at 1000°C; after cooling to room temperature, make the conversion rate 100% to obtain sintered calcium oxide. The conversion rate is calculated as follows: Y = △m / 44%m, where △m is the mass difference between calcium carbonate before and after calcination; m is the mass of calcium carbonate.

[0148] (2) Add 20% by volume (based on the volume of the reactor (5L)) of a metal salt base liquid to the reaction tank. The metal salt base liquid is sodium sulfate. The amount of sodium introduced is calculated based on the generated sodium oxide. The sodium oxide accounts for 5.7% of the total mass of the bioactive glass material. The reaction temperature is 80°C. The acid and alkali are added simultaneously. The pH value of the process is maintained at 8. The reaction time is 1.2 hours. The alkali used is sodium silicate with a modulus of 3.5 and a concentration of 2.2N. Based on the silicon dioxide generated by the alkali metal silicate accounting for 45% of the total mass of the bioactive glass material, a corresponding amount of alkali metal silicate is added. The acid used is phosphoric acid with a concentration of 6N. The generated phosphorus pentoxide accounts for 6% of the total mass of the bioactive glass material.

[0149] After the reaction is completed, the sintered calcium oxide from step (1) is added; the amount of sintered calcium oxide added is 24% of the total mass of the bioactive glass material, and the mixture is stirred at a speed of 600 rpm for 20 minutes until it is evenly stirred; then sodium hydroxide is added, the sodium introduced by the sodium hydroxide is calculated as sodium oxide generated, and the sodium oxide accounts for 6% of the total mass of the bioactive glass material. The mixture is stirred at a speed of 600 rpm for 30 minutes before discharging.

[0150] (3) The discharged liquid is spray dried with an inlet air temperature of 300° C. and an outlet air temperature of 120° C., and crushed to a desired particle size to obtain a bioactive glass material.

[0151] The bioactive glass material prepared in this embodiment was analyzed and identified by X-ray diffraction (XRD) analysis using a Bruker D8A A25 X-ray diffractometer, using Cu-Kα radiation, and had the following characteristic peaks represented by angle 2θ: 2θ=20.7±0.2°, 2θ=22.0±0.2°, 2θ=23.6±0.2°, 2θ=23.8±0.2°, 2θ=26.8±0.2°, 2θ=33.6±0.2°, 2θ=34.2±0.2°; 2θ=48.6±0.2°. The X-ray diffraction pattern of the bioactive glass material prepared in this embodiment is shown in FIG. Figure 4 shown.

[0152] Bioactive glass materials belong to Na 2 O-CaO-SiO 2 -P 2 O 5 System, by weight percentage, bioactive glass materials include: SiO 2 45%, P 2 O 5 6%, CaO 24%, Na 2 O 25%.

[0153] Example 6

[0154] (1) Preparation of reaction liquid A: Calcium carbonate is calcined to obtain calcium oxide (refer to Example 1), and the calcined calcium oxide is prepared into a calcium hydroxide slurry with a concentration of 0.8 mol / L, where the introduced calcium is calculated as the generated calcium oxide, and the calcium oxide accounts for 6% of the total mass of the bioactive glass material. The temperature is raised to 85° C., and a dilute phosphoric acid solution is added dropwise to the calcium hydroxide slurry, and a corresponding mass of dilute phosphoric acid is added, where the generated phosphorus pentoxide accounts for 4% of the total mass of the bioactive glass material, and the concentration of the dilute phosphoric acid solution is 38%, until the pH of the reaction is 7-9, and the reaction time is 2 h. After the reaction is completed, the mixture is aged and allowed to stand at room temperature for 2 h for use.

[0155] (2) Preparation of reaction liquid B: Add 10% by volume (based on the volume of the reactor (5 L)) of silica slurry to the reaction tank, the silicon introduced is calculated as the generated silica, and the silica accounts for 60% of the total mass of the bioactive glass material. Then add calcined calcium oxide, and the calcined calcium oxide accounts for 12% of the total mass of the bioactive glass material. Stir at a speed of 600 rpm for 30 minutes, then add sodium hydroxide, and the sodium introduced by the sodium hydroxide is calculated as the generated sodium oxide, and the sodium oxide accounts for 18% of the total mass of the bioactive glass material. Stir at a speed of 600 rpm for 4 hours and set aside.

[0156] (3) After mixing material A and material B evenly, drying them in an oven at 110° C. until the moisture content is less than 3%, and crushing them to obtain a bioactive glass material.

[0157] The bioactive glass material prepared in this embodiment was analyzed and identified by X-ray diffraction (XRD) using a Bruker D8A A25 X-ray diffractometer, using Cu-Kα radiation, and had the following characteristic peaks represented by angle 2θ: 2θ=20.2±0.2°, 2θ=23.8±0.2°, 2θ=26.5±0.2°, 2θ=26.8±0.2°, 2θ=33.6±0.2°, 2θ=34.2±0.2°, 2θ=48.6±0.2°. The X-ray diffraction pattern of the bioactive glass material prepared in this embodiment is shown in FIG. Figure 5 shown.

[0158] Bioactive glass materials belong to Na 2 O-CaO-SiO 2 -P 2 O 5 System, by weight percentage, bioactive glass materials include: SiO 2 60%, P 2 O 5 4%, CaO 18%, Na 2 O 18%.

[0159] Comparative Example 1

[0160] This comparative example uses the existing bioglass Novamin4516, which includes, by mass percentage: Na 2 O24.5wt%, CaO 24.5wt%, P 2 O 5 6.0wt%SiO 2 45wt%.

[0161] Bioglass Novamin4516 was analyzed and identified by X-ray diffraction (XRD) using a Bruker D8A A25 X-ray diffractometer, using Cu-Kα radiation. The X-ray diffraction pattern of bioglass Novamin4516 is shown in Figure 6 As shown. Figure 6 It can be seen that the X-ray diffraction pattern of bioglass Novamin4516 has no characteristic peaks and has an amorphous structure.

[0162] Comparative Example 2

[0163] The bioactive glass material used in this comparative example was prepared in powder form according to the method described in Example 2 of the patent application with patent publication number CN111017934A.

[0164] X-ray diffraction (XRD) analysis was performed using a Bruker D8A A25 X-ray diffractometer using Cu-Kα radiation. The X-ray diffraction pattern of the bioactive glass material of Comparative Example 2 is as follows: Figure 7 As shown. Figure 7 It can be seen that the X-ray diffraction spectrum of the bioactive glass material prepared in this comparative example has no characteristic peaks and is an amorphous structure.

[0165] Test Case

[0166] (1) Artificial saliva mineralization experiment

[0167] The bioactive glass prepared in Example 1, Comparative Example 1 and Comparative Example 2 was subjected to an artificial saliva mineralization experiment. Experimental steps: 0.60 g of sample was taken in a 100 mL beaker, commercially available artificial saliva was added to the 100 mL mark, and the mixture was stored at a constant temperature of 37°C, and the artificial saliva was replaced every 24 hours. The experiments were conducted for 1 day, 3 days, and 7 days respectively, and the experimental samples were numbered as A, B, and C, and energy spectrum analysis was performed to detect the change in the Ca / P molar content ratio. At the same time, the reaction product was subjected to XRD test.

[0168] If the Ca / P molar content ratio gradually decreases with the increase of artificial saliva mineralization time during the artificial saliva mineralization experiment, it means that the phosphorus element in the saliva has reacted chemically with the calcium element in the bioglass; if the Ca / P molar content ratio gradually approaches 1.67, it is speculated that hydroxyapatite may have been generated.

[0169] Table 2

[0170] Artificial saliva mineralization time 1d 2d 3d Example 1 2.759 1.96 1.68 Comparative Example 1 2.964 2.124 1.81 Comparative Example 2 2.925 3.2 2.536

[0171] The results of the artificial saliva mineralization experiment are shown in Table 2. As can be seen from Table 2, the Ca / P molar content ratio of the bioactive glass prepared in Example 1 of the present invention gradually approaches 1.67 with the increase of artificial saliva mineralization time, and it is speculated that hydroxyapatite may be generated, while the Ca / P molar content ratio of the bioactive glass of Comparative Examples 2 and 3 after artificial saliva mineralization is still somewhat different from 1.67.

[0172] The X-ray diffraction patterns of the products of the bioactive glass materials in Example 1, Comparative Example 1 and Comparative Example 2 after artificial saliva mineralization are shown as follows: Figure 8 , Fig. 9 and Fig.10 As shown. Figure 8 It can be seen that the X-ray diffraction spectrum of the product of the bioactive glass material prepared in Example 1 after artificial saliva mineralization has a characteristic peak of 2θ=34.2358°, which corresponds to the characteristic diffraction peak of hydroxyapatite, indicating that the bioactive glass material provided by the present invention generates hydroxyapatite after artificial saliva mineralization. Fig. 9 and Fig.10 It can be seen that the products of the bioactive glass after mineralization in Comparative Examples 2 and 3 have no characteristic peaks and are amorphous products without any hydroxyapatite crystals produced.

[0173] (2) Experiment on mineralization and occlusion of dentinal tubules by bioglass toothpaste

[0174] According to weight percentage, the bioglass toothpaste includes: 0.95% carbomer 940, 21.25% PEG-400, 0.2% saccharin sodium, 0.2% methylparaben, 55% glycerol, 3% ZI-165, 11% core-shell type, 2% K12, 5% bioglass, 0.5% titanium dioxide, and 0.9% flavor.

[0175] 1. Test method:

[0176] 1.1 Preparation of dentin samples: Cut and polish freshly extracted bovine incisors to make 12 dentin blocks of approximately 5 mm × 5 mm × 2 mm in size, corrode with 40% orthophosphoric acid for 20 minutes, rinse and corrode with 5% sodium hypochlorite for 5 minutes, and finally ultrasonically clean with deionized water for 20 minutes. Observe under a polarized light microscope to ensure that the dental tubules are fully exposed.

[0177] 1.2 Grouping: The 12 dentin samples were randomly divided into blank control group, experimental group 1, experimental group 2, and experimental group 3, with 3 pieces in each group.

[0178] 1.3 Preparation of toothpaste slurry: Weigh a certain amount of toothpaste and artificial saliva in a ratio of 1:1.6 (toothpaste: saliva), and weigh the toothpaste directly on the toothbrush head; the toothbrush head uses the most basic ORALB brush head.

[0179] 1.4 Partitioning: Use tape to stick half of the dentin sample (about 5 mm × 2.5 mm) as the non-treated area, and the other half (about 5 mm × 2.5 mm) as the experimental treatment area.

[0180] 1.5 Dentin cycle treatment: The blank control group was treated with deionized water, the experimental group 1 was treated with the bioglass toothpaste prepared by the bioactive glass material prepared in Example 1, the experimental group 2 was treated with the bioglass toothpaste prepared by the bioactive glass material of Comparative Example 2, and the experimental group 3 was treated with the bioglass toothpaste prepared by the bioactive glass material prepared in Comparative Example 1. Brush your teeth with an electric toothbrush for 3 minutes, then rinse thoroughly with deionized water, and then soak in artificial saliva, kept warm at 37°C. Repeat brushing for 3 minutes, then rinse thoroughly with deionized water, and then soak in artificial saliva, 2 times / d; take the dentin sample after brushing for 1 day and observe it with a scanning electron microscope.

[0181] 4.6 Drying: The dentin samples after cycle treatment were dried in a constant temperature oven at 25°C for 24 h.

[0182] 4.7 Scanning electron microscope observation: The dried dentin was sprayed with gold, and then the conditions before and after sealing were observed under a scanning electron microscope.

[0183] The experimental diagrams of the mineralization and occlusion of dentinal tubules experiment using the bioglass toothpaste prepared from the bioactive glass materials of Example 1, Comparative Example 1 and Comparative Example 2 are shown respectively as follows: Fig.11 , Fig.12 and Fig.13 As shown. Fig.11 , Fig.12 and Fig.13 It can be seen that the effect of mineralization and blocking of dentinal tubules by the bioglass toothpaste prepared by the bioactive glass material prepared in Example 1 is significantly better than that in Comparative Example 1 and Comparative Example 2, and a "bulge" is formed in Example 1; Comparative Example 1 and Comparative Example 2 do not block the dentinal tubules well, and some pores of the dentinal tubules are still exposed, and the blocking effect of Comparative Example 1 is significantly worse than that of Comparative Example 2.

[0184] (3) Experiment on the reaction rate between bioglass toothpaste and tooth surface

[0185] 0.50 g of the bioactive glass material of Example 1, Comparative Example 1 and Comparative Example 2 was placed in a 50 mL centrifuge tube, deionized water was added to the 50 mL mark, and the tube was stored at a constant temperature of 37° C. The supernatant was centrifuged at different time points to detect the content of silicon, calcium, phosphorus and sodium elements therein; a plasma spectrometer was used to analyze the concentration of silicon, calcium, phosphorus and sodium elements in a 0.01% bioglass aqueous solution at different time points. The results of Example 1, Comparative Example 1 and Comparative Example 2 are shown in Table 3, Table 4 and Table 5, respectively.

[0186] Table 3

[0187] time Silicon (ppm) Calcium (ppm) Phosphorus (ppm) Sodium (ppm) 1h 15.3 5.3 2.4 8.3 2h 18.1 7.6 2.0 10.1 4h 19.7 9.1 1.9 11.4 8h 20.5 10.9 1.5 14.8 12h 24.8 14.7 1.1 15.2 24h 25.7 15.5 0.6 16.8

[0188] Table 4

[0189]

[0190]

[0191] Table 5

[0192] time Silicon (ppm) Calcium (ppm) Phosphorus (ppm) 1h 13.4 4.2 1.4 2h 14.3 6.8 1.8 4h 16.5 9.3 1.9 8h 17.8 13.9 1.0 12h 19.5 17.4 0.8 24h 22.9 20.7 0.6

[0193] It can be seen from Tables 3, 4 and 5 above that the bioglass toothpaste formed by the bioactive glass material prepared by the present invention has a dissolution concentration of 15.3ppm for silicon, 5.3ppm for calcium, 2.4ppm for phosphorus and 8.3ppm for sodium at 1h. At 12h, the dissolution concentration of silicon is 24.8ppm, the dissolution concentration of calcium is 15.5ppm, the dissolution concentration of phosphorus is 0.6ppm and the dissolution concentration of sodium is 16.8ppm.

[0194] In the bioactive glass material of Comparative Example 1, the dissolution concentration of silicon is 9.2ppm, the dissolution concentration of calcium is 3.1ppm, the dissolution concentration of phosphorus is 1.0ppm, and the dissolution concentration of sodium is 5.3ppm at 1h. The dissolution rate of the bioactive glass material of Comparative Example 1 at 1h is far from the dissolution rate of the bioactive glass material of the present invention.

[0195] The bioactive glass material in Comparative Example 2 has a dissolution concentration of 13.4 ppm silicon, 4.2 ppm calcium and 1.4 ppm phosphorus in 1 hour. The dissolution rate of the bioactive glass material of the present invention is also better than that of the bioactive glass material in Comparative Example 2.

[0196] The above results indicate that, compared with existing bioactive glasses, the silicon, calcium, phosphorus and sodium elements in the bioactive glass material provided by the present invention have a more excellent dissolution rate, and thus can generate a silicon glass network in water or body fluids more quickly, while calcium and phosphorus can also be released to the tooth surface more quickly, and crystallize into mixed hydroxyl-carbonate apatite on the surface; deposited on the tooth surface, mineralization occurs to seal exposed dentinal tubules, and the reaction can be faster with the tooth surface to achieve remineralization of the dentin surface, thereby alleviating or treating dentin sensitivity.

[0197] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A bioactive glass material, characterized in that: The bioactive glass material belongs to the Na2O-CaO-SiO2-P2O5 system, and comprises, by weight percentage, 40-60% SiO2, 1-10% P2O5, 18-30% CaO, and 10-30% Na2O; the X-ray diffraction spectrum of the bioactive glass material comprises the following diffraction peaks with 2θ angle values: 33.6±0.2°, 34.2±0.2°.

2. The bioactive glass material according to claim 1, characterized in that: The X-ray diffraction pattern of the bioactive glass material comprises diffraction peaks at the following 2θ angle values: 20.2±0.2°, 23.8±0.2°, 26.5±0.2°, 26.8±0.2°, 33.6±0.2°, 34.2±0.2° and 48.6±0.2°.

3. The bioactive glass material according to claim 1, characterized in that: The X-ray diffraction pattern of the bioactive glass material comprises diffraction peaks at the following 2θ angle values: 19.1±0.2°, 20.2±0.2°, 20.7±0.2°, 22.0±0.2°, 23.6±0.2°, 23.8±0.2°, 26.5±0.2°, 26.8±0.2°, 26.9±0.2°, 31.9±0.2°, 32.1±0.2°, 33.6±0.2°, 34.2±0.2° and 48.6±0.2°.

4. The bioactive glass material according to claim 1, characterized in that: The bioactive glass material has an X-ray diffraction pattern consistent with FIG. 1 , FIG. 4 or FIG. 5 .

5. The method for preparing the bioactive glass material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) adding alkali metal silicate and inorganic acid in a co-dropping process, maintaining the solution pH at 2-6 and the reaction temperature at 40-95° C. during the co-dropping process; or Alkali metal silicate and inorganic acid are used to perform acid-base co-dropping in the metal salt base solution, and the solution pH is maintained at 2-6 during the co-dropping process, and the reaction temperature is 40-95°C; (2) After the reaction in step (1) is completed, calcium oxide is added and stirred; phosphoric acid is added for reaction and stirred; and then sodium-containing alkali solution is added and stirred to prepare a bioactive glass material.

6. The method for preparing the bioactive glass material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) adding alkali metal silicate and phosphoric acid in a co-dropping process, maintaining the solution pH at 3-10 and the reaction temperature at 40-95° C. during the co-dropping process; or Alkali metal silicate and phosphoric acid are used in the metal salt base solution for acid-base co-dropping, and the solution pH is maintained at 3-10 during the co-dropping process, and the reaction temperature is 40-95°C; (2) After the reaction in step (1) is completed, calcium oxide is added and stirred; then, an alkali solution containing sodium is added and stirred; and a bioactive glass material is prepared.

7. The method for preparing the bioactive glass material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Mixing calcium hydroxide slurry and phosphoric acid at 40-95°C for reaction, maintaining pH at 7-9 during the reaction; performing aging treatment after the reaction to obtain reaction liquid A; S2. The silica slurry and calcium oxide are mixed and stirred; then a sodium-containing alkali solution is added and stirred to obtain a reaction solution B; S3. Mix the reaction liquid A and the reaction liquid B, and dry them to obtain a bioactive glass material.

8. Use of the bioactive glass material according to any one of claims 1 to 4 in blocking dentinal tubules or in preparing an oral care composition.

9. An oral care composition, characterized in that Calculated by weight percentage, it comprises: 0.1-20% of the bioactive glass material according to any one of claims 1-4 and orally acceptable auxiliary materials.

10. A toothpaste, characterized in that: The invention comprises, by weight: 1-10 parts of the bioactive glass material according to any one of claims 1 to 4, 20.5-26.5 parts of a thickener, 45-60 parts of a wetting agent, 11-20 parts of a friction agent, 1-5 parts of a foaming agent, 0-3 parts of a colorant, 0-3 parts of a flavoring agent, 0-0.5 parts of a sweetener, and 0-0.5 parts of an antibacterial agent.

Citation Information

Patent Citations

  • Bioactive glass ceramic material and preparation method and application thereof in oral care products

    CN103449725A

  • Toothpaste with phosphosilicate glass

    CN108403453A

  • Bioactive glass

    CN111494218A

  • Friction type silicon dioxide for low-refraction high-cleanness toothpaste and preparation method of friction type silicon dioxide

    CN112408406A

  • Bioactive glass as well as preparation method and application thereof

    CN114804624A

Cited By

  • Composition for repairing enamel and preparation method thereof

    CN120983274A